Model Pengelolaan Pembelajaran Berbasis Adab Sebagai Fondasi Pembentukan Karakter Mahasiswa Di Institut Agama Islam Hasanuddin Pare kediri - Ahmad Rifai; Didik Andriawan; Ahmad Natsir Fitriono (PT. Saha Kreasi Indonesia, 2025)
The quality of student character in the digital era has experienced a decline, as evidenced by the weakening of manners, discipline, and academic integrity. This situation highlights the need for an approach to learning management that not only focuses on cognitive aspects but also emphasizes values of etiquette. This study aims to describe a values-based learning management model as a foundation for character development among university students. By employing a descriptive qualitative method, data were collected through classroom observations, interviews with lecturers and students, as well as analysis of course syllabi. The research findings reveal that the values-based learning management model encompasses four components: values-oriented planning, implementation of learning that emphasizes exemplary behavior, humanistic and polite classroom interaction management, and character evaluation integrated with academic assessment. This model has been shown to have a positive impact on enhancing student discipline, integrity, and communication ethics. The study recommends the integration of values of etiquette into the curriculum and policies of higher education institutions to strengthen student character comprehensively.